2017
DOI: 10.1039/c7em00059f
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis and cellular toxicities of the organic ultraviolet filter chemical octyl methoxycinnamate and its photoproducts

Abstract: Organic ultraviolet filter chemicals (UVFCs) are the active ingredients used in many sunscreens to protect the skin from UV light; these chemicals have been detected in numerous aquatic environments leading to concerns about how they might affect aquatic organisms and humans. One commonly used organic UVFC is octyl methoxycinnamate (OMC), better known by its commercial name, octinoxate. Upon exposure to UV light, OMC degrades rapidly, forming numerous photoproducts, some of which have been previously identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“… Stein et al isolated and characterized the cellular toxicities of the major products of UV‐induced photolysis of octinoxate. They reported that the parent compound and two cyclodimer photoproducts are toxic to cells (NIH/3T3). Danovaro et al conducted several independent in situ studies on several species of coral in different areas of the world.…”
Section: Commentarymentioning
confidence: 99%
“… Stein et al isolated and characterized the cellular toxicities of the major products of UV‐induced photolysis of octinoxate. They reported that the parent compound and two cyclodimer photoproducts are toxic to cells (NIH/3T3). Danovaro et al conducted several independent in situ studies on several species of coral in different areas of the world.…”
Section: Commentarymentioning
confidence: 99%
“…Previous neutral red cell cytotoxicity assay using NIH/3T3 cells showed that trans-EHMC, cis-EHMC, 4-MBA, and the two cyclodimers produced are toxic to cells, reducing cellular viabilities to 8-69%, depending on the concentrations used (Stein et al, 2017). In contrast, the 2-EH photodegradation product is not harmful to cells, demonstrating that different photoproducts contribute differently to the overall toxicity of EHMC photolysate (Stein et al, 2017).…”
Section: Ethylhexyl Methoxycinnamatementioning
confidence: 99%
“…When exposed to sunlight, both OMC isomers form photoproducts (4-methoxybenzaldehyde (4-MBA) and 2-ethylhexanol (2-EH)) that can further may dimerize in various cyclodimers (MacManus-Spencer et al 2011). These photoproducts, including cyclodimers, have different levels of cellular toxicity and may even be more toxic than OMC itself (Duale et al 2010;Stein et al 2017). They can sensitize singlet oxygen ( 1 O 2 ) and lead to ROS formation, but this mechanism needs to be explored (Hanson et al 2006;Hanson et al 2015).…”
Section: Uv-b Filter Octylmethoxycinnamate Photoinstabilitymentioning
confidence: 99%